A Novel Polyphosphate‐Degrading Enzyme Confers Growth on Exogenous Polyphosphate in the Archaeon Haloferax volcanii - Jack W. F. Nicholls; Vincent O'Flaherty; Timothy M. Lenton; John W. McGrath; Jason P. Chin (Environmental Microbiology, 2026)
Polyphosphate (polyP) is an inorganic biopolymer of orthophosphate (Pi) that plays roles in many central biochemical processes in microorganisms, including acting as a cellular reservoir of phosphorus. The microbial metabolism of polyP is considered limited to its intracellular cycling by kinases and exopolyphosphatases. However, little is known about polyP metabolism in the Archaea. Notably, many haloarchaea, including Haloferax volcanii , encode homologues of bacterial polyP‐synthesising genes, but lack the corresponding genes for its catabolism. Here, we show that H. volcanii possesses a novel polyP‐degrading enzyme with characteristics distinguishing it from currently known enzymes. This activity also enabled H. volcanii to grow on exogenous polyP as its sole source of phosphorus. Activity was localised to a discrete protein band by native‐PAGE zymography and enzyme assays of cell‐free extracts from cells grown on polyP revealed the enzyme was halophilic, required Mn 2+ or Co 2+ and released Pi from polyP. No activity was observed in the extracellular medium of cells grown on polyP, suggesting the enzyme is either membrane‐bound or intracellular. These findings thus broaden our understanding of the potential ecological roles of polyP in the biogeochemical cycling of phosphorus, and our understanding of the enzymes and pathways involved in archaeal polyP metabolism.

Effects of Pig Slurry Treatment with a Peroxide-Based Additive, GasAbate, on the Seasonal Growth of Perennial Ryegrass - W. K. O’Neill; C. E. Thorn; P. Williams; D. Hughes; J. Chin; S. Nolan; V. O’Flaherty; J. McGrath (Journal of Soil Science and Plant Nutrition, 2026)
Livestock manures are valuable sources of crop nutrients, however greenhouse gas (GHG) emissions during storage exacerbate climate change and also preclude the closing of nutrient loops. Chemical additives applied during storage can reduce these emissions, where a peroxide-based slurry additive (GasAbate) successfully reduces GHG emissions from stored pig slurry. However, its effects upon crop uptake, and thus plant yields, following land application have not been assessed. To this end, a 5-month pot trial was used to assess ryegrass dry matter (DM) after fertilisation with either untreated (SU) or GasAbate treated (ST) pig slurry post-storage (4 replicates per condition), where an organic topsoil and a heavy gley soil were assessed. Pots were stored under ambient, outdoor conditions and four harvests were performed for DM and grass quality, inferred by measuring chlorophyll content. In both soil types, DM yields across four harvests were consistently higher. In the high OM soil the cumulative yield from ST (122.50 g DM pot⁻ 1 ) exceeded that from SU (101 g DM pot⁻ 1 ) equating to a 21.2% increase ( p < 0.05). In the second, lower OM soil, cumulative yields were lower but again cumulative ST yields (109.0 g DM pot⁻ 1 ) exceeded those from SU (90.6 g DM pot⁻ 1 ) representing a 20.3% increase ( p < 0.05). Chlorophyll indices demonstrated that, in one soil type, ST resulted in grass with higher ( p < 0.05) chlorophyll content which would increase the nutritional value of the pasture. In the two soils tested, GasAbate-treated pig slurry improved ryegrass DM yields, while an increase in chlorophyll content was observed in one soil type. These preliminary findings highlight the additive’s ability to slow the nutrient loss typically seen during slurry storage and potentially improve agricultural circularity.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Incognito forms of polyethylene small micro and nanoplastics in solvents: Changes in molecular vibrations - Julie R. Peller; Noah Durlam; Yanni Flaherty; Abbie Valicevic; Christina M. Davis; Shelby Watson; Julien E. Tournebise; Juan A. Medina-Garcia; Mark Dadmun; Stephen P. Mezyk (Science of The Total Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Streptomyces hygroscopicus and rapamycinicus Evaluated from a U.S. Marine Sanctuary: Biosynthetic Gene Clusters Encode Antibiotic and Chemotherapeutic Secondary Metabolites - Hannah R. Flaherty; Semra A. Aytur; John P. Bucci (Journal of Marine Science and Engineering, 2024)
Cancer remains a leading cause of death worldwide. Also threatening the public is the emergence of antibiotic resistance to existing medicines. Despite the challenge to produce viable natural products to market, there continues to be a need within public health to provide new chemotherapeutic drugs such as those exhibiting cytotoxicity and tumor cell growth-inhibitory properties. As marine genomic research advances, it is apparent that marine-derived sediment harbors uniquely potent bioactive compounds compared to their terrestrial counterparts. The Streptomyces genus in particular produces more than 30% of all secondary metabolites currently approved for human health, thus harboring unexplored reservoirs of chemotherapeutic and antibiotic agents to combat emerging disease. The present study identifies the presence of Streptomyces hygroscopicus and rapamycinicus in environmental sediment at locations within the U.S. Stellwagen Bank National Marine Sanctuary (SBNMS) from 2017 to 2022. Sequencing and bioinformatics methods catalogued biosynthetic gene clusters (BGCs) that drive cytotoxic and antibiotic biochemical processes in samples collected from sites permittable and protected to fishing activity. Poisson regression models confirmed that Sites 1 and 3 had significantly higher occurrences of rapamycinicus than other sites (p F crit).

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Temporal variations in the diversity of primitive melts supplied to the Santorini silicic magmatic system and links to lithospheric stresses - T. Flaherty; T. H. Druitt; L. Francalanci; P. Schiano; O. Sigmarsson (Contributions to Mineralogy and Petrology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Excluding mammalian predators increases bird densities and seed dispersal in fenced ecosanctuaries - Sara P. Bombaci; John Innes; Dave Kelly; Victoria Flaherty; Liba Pejchar (Ecology, 2021)
Islands are epicenters of animal extinctions and population declines. These losses exacerbate biodiversity loss and disrupt ecological services in areas of high endemism. Island defaunation is primarily driven by invasive mammalian predators, and mammal eradications are reversing population declines for some island species. Invasive mammal eradications may also have the capacity to restore ecological interactions, along with the recovery of island fauna. Here we show that invasive mammal eradication in fenced ecosanctuaries results in higher rates of bird foraging on fruit, and higher bird‐mediated seed dispersal, than in similar forests without mammal eradication. We further show that higher foraging and seed dispersal is related to higher densities of native bird species, after accounting for natural variation in fruit availability. For the many other systems globally that are under threat from invasive mammals, New Zealand’s fenced ecosanctuary model offers a promising tool for restoring biodiversity and ecosystem services.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Evaluation of Structured and Unstructured Models for Application in Operational Ocean Forecasting in Nearshore Waters - Shannon Nudds; Youyu Lu; Simon Higginson; Susan P. Haigh; Jean-Philippe Paquin; Mitchell O’Flaherty-Sproul; Stephanne Taylor; Hauke Blanken; Guillaume Marcotte; Gregory C. Smith; Natacha B. Bernier; Phillip MacAulay; et al. (Journal of Marine Science and Engineering, 2020)
The oceanography sub-initiative of Canada’s Oceans Protection Plan was tasked to develop high-resolution nearshore ocean models for enhanced marine safety and emergency response, fitting into the multi-scale, multi-level nested operational ocean forecasting systems. For decision making on eventual 24/7 operational support, two ocean models (a structured grid model, NEMO (Nucleus for European Modelling of the Ocean); and an unstructured grid model, FVCOM (Finite Volume Coastal Ocean Model), were evaluated. The evaluation process includes the selection of the study area, the requirements for model setup, and the evaluation metrics. The chosen study area, Saint John Harbour in the Bay of Fundy, features strong tides, significant river runoff and a narrow tidal-river channel. Both models were configured with the same sources of bathymetry and forcing data. FVCOM achieved 50-100 m horizontal resolution in the inner harbour and included wetting/drying. NEMO achieved 100 m resolution in the harbour with a three-level one-way nesting configuration. Statistical metrics showed that one-year simulations with both models achieved comparable accuracies against the observed tidal and non-tidal water levels and currents, temperature and salinity, and the trajectories of surface drifters, but the computational cost of FVCOM was significantly less than that of NEMO.

Pheromone-enhanced lure blends and multiple trap heights improve detection of bark and wood-boring beetles potentially moved in solid wood packaging - L. Flaherty; J. M. G. Gutowski; C. Hughes; P. Mayo; T. Mokrzycki; G. Pohl; P. Silk; K. Van Rooyen; J. Sweeney (Journal of Pest Science, 2019)

Molecular characterization of an allelic series of mutations in the mouse Nox3 gene - John P. Flaherty; Heather E. Fairfield; Catrina A. Spruce; Christopher M. McCarty; David E. Bergstrom (Mammalian Genome, 2011)

Quadrupedal locomotor performance in two species of arboreal squirrels: predicting energy savings of gliding - Elizabeth A. Flaherty; Merav Ben-David; Winston P. Smith (Journal of Comparative Physiology B, 2010)

Amphibian Chemical Defense: Antifungal Metabolites of the Microsymbiont Janthinobacterium lividum on the Salamander Plethodon cinereus - Robert M. Brucker; Reid N. Harris; Christian R. Schwantes; Thomas N. Gallaher; Devon C. Flaherty; Brianna A. Lam; Kevin P. C. Minbiole (Journal of Chemical Ecology, 2008)

eNOS Deficient Mice Develop Progressive Cardiac Hypertrophy with Altered Cytokine and Calcium Handling Protein Expression - Michael P. Flaherty; Maria Brown; Ingrid L. Grupp; Jo El Schultz; Sidney S. Murphree; W. Keith Jones (Cardiovascular Toxicology, 2007)

Mathematical Models of Cell Motility - Brendan Flaherty; J. P. McGarry; P. E. McHugh (Cell Biochemistry and Biophysics, 2007)

Preface - Vincent O'Flaherty; Therese Mahony; Anthony P. Moran; Piet Lens (Reviews in Environmental Science and Bio/Technology, 2003)

Variations in microbial populations in soils with different methane uptake rates - T.W. Willison; M.S. O'Flaherty; P. Tlustos; K.W.T. Goulding; D.S. Powlson (Nutrient Cycling in Agroecosystems, 1997)